KI 2020 : advances in artificial intelligence : 43rd German Conference on AI, Bamberg, Germany, September 21-25, 2020, Proceedings /: advances in artificial intelligence : 43rd German Conference on AI, Bamberg, Germany, September 21-25, 2020, Proceedings. (2020) - Unknown
No abstract available